A rare potentially treatable cause of bilateral optic disc swelling. (13th October 2010) - Abu-Ain, M; Aazem, S; Morton, C; Kumwenda, M; Griffiths, D; Jacob, A
Abstract : Rapid onset bilateral optic disc swelling generally indicates an intracranial problem—that is, papilloedema. However, when there is also visual loss, disease affecting the optic nerves themselves must be considered. We present the diagnostic problem of a patient with optic disc swelling and progressive visual loss. Investigations finally revealed hypocalcaemia secondary to primary hypoparathyroidism. With treatment a marked improvement in vision occurred. This reversible rare cause of optic disc swelling should not be forgotten.